Effect of four different hamstring and quadriceps training protocols on explosive strength - Ortiz, A. M.; Delgado, D. V.; Val, S. L. (Apunts Sports Medicine, 2021)
Introduction: The main objective of this study was to analyze more effective muscle work on some explosive strength performance variables. The secondary objectives were to determine how gender influences results and influence of the muscle work type on physiological parameters.